1989
DOI: 10.1007/bf01745343
|View full text |Cite
|
Sign up to set email alerts
|

Histaminwirkungen am Herzen unter besonderer Berücksichtigung kardialer Nebenwirkungen von H2-Rezeptor-Antagonisten

Abstract: The existence of cardiac h1- and h2-receptors is evidenced by pharmacologic studies. Despite of the relatively high content of cardiac histamine it is not clarified whether histamine actually plays a physiologic role - apart from pharmacologic effects - in the regulation of myocardial function and coronary blood flow. Under pathophysiologic conditions (during anaphylaxis, surgical procedures, accidents, stress etc.), however, when a local or systemic histamine release occurs both hemodynamic and arrhythmogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…[3][4][5][6] The underlying mechanism involves the action on the H2 receptors at the sinus node and atrial tissue in the heart. 7,8 Through these receptors, they exert positive chronotropic and inotropic effects on the heart.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The underlying mechanism involves the action on the H2 receptors at the sinus node and atrial tissue in the heart. 7,8 Through these receptors, they exert positive chronotropic and inotropic effects on the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac arrhythmias induced by activation of H 1 and H 2 receptors are among the most serious consequences of mast cell degranulation. Several studies have shown the effectiveness of a premedication with a combination of H 1 R and H 2 R antagonists, for example dimetindene plus cimetidine [10,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%